USE OF ANABOLIC HORMONE THERAPIES IN SARCOPENIA IN OLDER ADULTS: CURRENT EVIDENCE AND PROGNOSIS - Gomes, Celsilvana Teixeira; Döbele, Leonardo dos Santos; Guimarães, Eduardo Duarte; Salvadego, Matheus Alvino Liutti de Oliveira; Costa, Leandro Dias; Slaviero, Luiza; Rocha, Giovanna Maria Oliveira; Correia, Marcela Torquato Rocha; Prado Júnior, Nildo da Silva; Neglisoli, Vanessa; Delfino, Otávio de Meireles; Vilela, Ana Claudia Medeiros; et al. (Seven Editora, 2026)
Sarcopenia is a multifactorial condition associated with aging, characterized by the progressive loss of skeletal muscle mass and function, with significant impact on physical performance and quality of life in older adults. In this context, anabolic hormone therapies have been investigated as potential strategies to mitigate this process. This study aimed to critically analyze the current scientific evidence regarding the use of these therapies in the management of sarcopenia in older individuals. This is a narrative literature review conducted using PubMed, ScienceDirect, and SciELO databases, including publications from 2016 to 2026. A total of 17 studies were selected, addressing testosterone replacement therapy (TRT), selective androgen receptor modulators (SARMs), and other hormonal approaches. The findings indicate that TRT consistently improves lean body mass and body composition; however, its effects on physical function remain heterogeneous. SARMs show promising anabolic effects in experimental models, but clinical evidence is still limited. Additionally, relevant concerns persist regarding the safety of these interventions, particularly in relation to cardiovascular risk and long-term outcomes. In conclusion, despite favorable effects on structural parameters, anabolic hormone therapies do not yet have sufficient evidence to support their use as standard treatment for sarcopenia, highlighting the need for further studies focusing on functional outcomes and long-term safety.